Nursing students' perception on their clinical learning environment - Ahmad, Norfadzilah (IIUM Press, International Islamic University Malaysia, 2017)
Quality in academia and effective clinical learning are important factors in nursing education. Positive perception on clinical environment provides opportunity for students to gain appropriate knowledge in caring of the patient comprehensively, develop clinical judgement and critical thinking skills. The aim of an institution is to provide the best and highest quality of clinical education for the students; meaningful clinical experiences ensure competent nurse in the future.